Impact of the coronavirus disease 2019 (COVID-19) pandemic on the care of patients with acute and chronic aortic conditions. (4th January 2021) - Czerny, Martin; Gottardi, Roman; Puiu, Paul; Bernecker, Oliver Y; Citro, Rodolfo; Della Corte, Alessandro; di Marco, Luca; Fink, Martina; Gosslau, Yvonne; Haldenwang, Peter Lukas; Heijmen, Robin H; Hugas-Mallorqui, Maria; et al.
Abstract: : OBJECTIVES: To evaluate the impact of the coronavirus disease 2019 (COVID-19) pandemic on acute and elective thoracic and abdominal aortic procedures. METHODS: Forty departments shared their data on acute and elective thoracic and abdominal aortic procedures between January and May 2020 and January and May 2019 in Europe, Asia and the USA. Admission rates as well as delay from onset of symptoms to referral were compared. RESULTS: No differences in the number of acute thoracic and abdominal aortic procedures were observed between 2020 and the reference period in 2019 [incidence rates ratio (IRR): 0.96, confidence interval (CI) 0.89–1.04; P = 0.39]. Also, no difference in the time interval from acute onset of symptoms to referral was recorded (<12 h 32% vs > 12 h 68% in 2020, < 12 h 34% vs > 12 h 66% in 2019 P = 0.29). Conversely, a decline of 35% in elective procedures was seen (IRR: 0.81, CI 0.76–0.87; P < 0.001) with substantial differences between countries and the most pronounced decline in Italy (−40%, P < 0.001). Interestingly, in Switzerland, an increase in the number of elective cases was observed (+35%, P = 0.02). CONCLUSIONS: There was no change in the number of acute thoracic and abdominal aortic cases and procedures during the initial wave of the COVID-19 pandemic, whereas the case load of elective operations and procedures decreased significantly. Patients with acute aortic syndromes presented despite COVID-19 and were managed according to current guidelines. Further analysis is required to prove that deferral of elective cases had no impact on premature mortality.